ANALISIS KESESUAIAN LAHAN KOMODITAS UNGGULAN KOTA PARIAMAN - Aldeta, Abellia Fanny; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The aim of this research is to identify the flagship commodities and analyze the suitability of land for the flagship commodity subsector of food crops and plantations in the city of Pariaman. This research employs a quantitative descriptive method. The determination of flagship commodities utilizes parameters such as the production output of food crops and plantations in the city of Pariaman, as well as the productivity of food crops and plantations in the city of Pariaman. For land suitability assessment, matching and comparing characteristics such as temperature, root media (encompassing drainage and texture), nutrient retention, and slope are conducted using ArcGIS 10.8 software to determine the suitability of land for coconut and rice paddy cultivation. The research findings indicate that the flagship commodities of Pariaman City are rice paddy and coconut crops. There are four categories for rice paddy land suitability: highly suitable covering 95.7636 hectares (0.92%), moderately suitable covering 3,054.34 hectares (29.45%), marginally suitable covering 3,221.83 hectares (31.06%), and not suitable covering 4,000.25 hectares (38.56%). As for the coconut commodity, there are four categories: highly suitable covering 1,082.88 hectares (10.44%), moderately suitable covering 495.33 hectares (4.78%), marginally suitable covering 4,787.26 hectares (46.15%), and not suitable covering 3,995.5 hectares (38.51%).